What is Originality in the Humanities and the Social Sciences? - Guetzkow, Joshua; Lamont, Michèle; Mallard, Grégoire (American Sociological Review, 2004)
Drawing on interviews with peer-review panelists from five multidisciplinary fellowship competitions, this paper analyzes one of the main criteria used to evaluate scholarship in the humanities and the social sciences: originality. Whereas the literature in the sociology of science focuses on the natural sciences and defines originality as the production of new findings and new theories, we show that in the context of fellowship competitions, peer reviewers in the social sciences and humanities define originality much more broadly: as using a new approach, theory, method, or data; studying a new topic; doing research in an understudied area; or producing new findings. Whereas the literature has not considered disciplinary variation in the definition of originality, we identified significant differences. Humanists and historians clearly privilege originality in approach, and humanists also emphasize originality in the data used. Social scientists most often mention originality in method, but they also appreciate a more diverse range of types of originality. Whereas the literature tends to equate originality with substantive innovation and to consider the personal attributes of the researcher as irrelevant to the evaluation process, we show that panelists often view the originality of a proposal as an indication of the researcher's moral character, especially of his/her authenticity and integrity. These contributions constitute a new approach to the study of peer review and originality that focuses on the meaning of criteria of evaluation and their distribution across clusters of disciplines.